Clima escolar y oralidad en estudiantes de educación secundaria de la institución educativa primaria y secundaria Nº 60053 Gral. Augusto Freyre García 2024 - Da Silva Sifuentes, Patricio Leao (2025)
The present study seeks to establish the relationship between school climate and orality in secondary school students of the Primary and Secondary School Nº 60053 Gral. Augusto Freyre García. The methodology used is basic and non-experimental cross-sectional design, collecting data by means of structured questionnaires applied to the students. According to the findings, 5% of the students rated the school climate variable as good, 93.8% as fair and a small 1.2% as bad. On the orality variable, it was rated as good by 25%, 73.8% considered it fair and only 1.2% rated it as bad. In addition, Spearman's Rho test showed a very high positive correlation of Rho= 0.996; likewise, the significance value was 0.000<0.05, in conclusion, school climate is significantly related to orality in Secondary Education students of the Primary and Secondary Educational Institution Nº 60053 Gral. Augusto Freyre García, 2024.